N-acetylcysteine (NAC) in schizophrenia resistant to clozapine: a double blind randomised placebo controlled trial targeting negative symptoms. Issue 1 (December 2016) - Rossell, Susan; Francis, Paul; Galletly, Cherrie; Harris, Anthony; Siskind, Dan; Berk, Michael; Bozaoglu, Kiymet; Dark, Frances; Dean, Olivia; Liu, Dennis; Meyer, Denny; Neill, Erica; et al.
Abstract Background Clozapine is an effective treatment for a proportion of people with schizophrenia (SZ) who are resistant to the beneficial effects of other antipsychotic drugs. However, anything from 40–60 % of people on clozapine experience residual symptoms even on adequate doses of the medication, and thus could be considered 'clozapine resistant'. Agents that could work alongside clozapine to improve efficacy whilst not increasing the adverse effect burden are both desired and necessary to improve the lives of individuals with clozapine-resistant SZ.N -Acetylcysteine (NAC) is one such possible agent. Previous research from our research group provided promising pilot data suggesting the efficacy of NAC in this patient population. The aim of the study reported here is to expand this work by conducting a large scale clinical trial of NAC in the treatment of clozapine-resistant SZ. Methods This study is an investigator initiated, multi-site, randomised, placebo-controlled trial. It aims to include 168 patients with clozapine-resistant SZ, divided into an intervention group (NAC) and a control group (placebo). Participants in the intervention group will receive 2 g daily of NAC. The primary outcome measures will be the negative symptom scores of the Positive and Negative Syndrome Scale (PANSS). Secondary outcome measures will include: changes in quality of life (QoL) as measured by the Lancashire Quality of Life Profile (LQoLP) and cognitive functioning as measured by the total score on the MATRICS. Additionally we will examine peripheral and cortical glutathione (GSH) concentrations as process outcomes. Discussion This large scale clinical trial will investigate the efficacy of NAC as an adjunctive medication to clozapine. This trial, if successful, will establish a cheap, safe and easy-to-use agent (NAC) as a 'go to' adjunct in patients that are only partly responsive to clozapine. Trial registration Australian and New Zealand Clinical Trials Registration Number: Current Randomised Controlled TrialACTRN12615001273572 . The date of registration 23 November 2015.